Evaluasi Pilkada Pelaksanaan Pilkada Serentak Tahun 2015 - Chaniago, Pangi Syarwi (Political Science Program, Universitas Negeri Semarang, 2016)
This study was carried out to evaluate the enforcement of the first direct district heads election in 2015, in order to promote the quality of democracy. This study applied qualitative method. There were several findings on this study; (1) direct district heads election has not been efficient yet; (2) direct district heads election has not been able to promote political participation; (3) direct district heads election has not been able to shut off money politic; (4) recruitment the election of district head candidates has not been transparant; (5) financing of direct election was not charged (appropriate) to Regional Government Budget; (6) Constitutional Court refused to adjudicate the dispute of election results if the margin of ballot more than 2%, it broke sense of justice; (7) the phenomenon of the emergence of a single candidate for district heads due to regulations, the must withdraw from candidacy for they were civil servants, military/police, House of Representatives, Regional Representative Board and Regional House of Representatives.